An All-Organic Proton Battery - Emanuelsson, Rikard; Sterby, Mia; Strømme, Maria; Sjödin, Martin (Journal of the American Chemical Society, 2017)
Rechargeable batteries that use organic matter as the capacity-carrying material have previously been considered a technology for the future. Earlier batteries in which both the anode and cathode consisted of organic material required significant amounts of conductive additives and were often based on metal-ion electrolytes containing Li or Na . However, we have used conducting poly(3,4-ethylenedioxythiophene) (PEDOT), functionalized with anthraquinone (PEDOT-AQ) or benzonquinone (PEDOT-BQ) pendant groups as the negative and positive electrode materials, respectively, to make an all-organic proton battery devoid of metals. The electrolyte consists of a proton donor and acceptor slurry containing substituted pyridinium triflates and the corresponding pyridine base. This slurry allows the 2e /2H quinone/hydroquinone redox reactions while suppressing proton reduction in the battery cell. By using strong (acidic) proton donors, the formal potential of the quinone redox reactions is tuned into the potential region in which the PEDOT backbone is conductive, thus eliminating the need for conducting additives. In this all-organic proton battery cell, PEDOT-AQ and PEDOT-BQ deliver 103 and 120 mAh g , which correspond to 78% and 75%, respectively, of the theoretical specific capacity of the materials at an average cell potential of 0.5 V. We show that PEDOT-BQ determines the cycling stability of the device while PEDOT-AQ provides excellent reversibility for at least 1000 cycles. This proof-of-concept shows the feasibility of assembling all-organic proton batteries which require no conductive additives and also reveals where the challenges and opportunities lie on the path to producing plastic batteries.